ER-residential Nogo-B accelerates NAFLD-associated HCC mediated by metabolic reprogramming of oxLDL lipophagy - Yuan Tian (Nature Portfolio, 2019)
Non alcoholic fatty liver disease (NAFLD) associates with an elevated risk of developing hepatocellular carcinoma (HCC). Here, the authors find that Nogo-B, an endoplasmic reticulum resident protein, is upregulated by lipid uptake and acts as an oncogene in NAFLD-associated HCC by promoting lipid droplet breakdown by lipophagy and triggering Hippo pathway dysregulation